Ethno-STEM Integrated Project-Based Learning to Improve Students’ Creative Thinking Skills - Babalola, Ebenezer Omolafe; Keku, Emmanuel (International Journal of Ethnoscience and Technology in Education, 2024)
This study investigates the impact of integrating Ethno-STEM with project-based learning (PjBL) on enhancing creative thinking skills among secondary school students in Nigeria. Acknowledging the critical role of creativity in STEM education, the research addresses the gap between traditional teaching methods and the need for innovative approaches that foster creative thinking. Traditional STEM education, often characterized by rote memorization, has been criticized for not adequately preparing students to tackle real-world problems innovatively. The incorporation of Ethno-STEM into PjBL represents an avant-garde pedagogical strategy, aimed at bridging cultural knowledge with scientific inquiry, thereby making learning more relevant, engaging, and effective in developing creative problem-solvers. This quasi-experimental study, conducted over four months, involved 84 students divided equally into an experimental group, which experienced the Ethno-STEM integrated PjBL, and a control group, which continued with conventional curriculum. Creative thinking skills were assessed through pretests and posttests, focusing on fluency, flexibility, and originality. The results demonstrated a significant improvement in the creative thinking abilities of the experimental group compared to the control group, indicating that the Ethno-STEM integrated PjBL approach effectively enhances students’ creative thinking skills. These findings underscore the potential of integrating cultural knowledge and project-based learning in STEM education to nurture innovation and creative problem-solving capabilities among students.